2009
DOI: 10.1007/s11071-009-9506-z
|View full text |Cite
|
Sign up to set email alerts
|

Limiting phase trajectories and energy exchange between anharmonic oscillator and external force

Abstract: We present a simple analytical description of transient vibrations of forced anharmonic oscillator in terms of periodic non-smooth functions. Such a description (in chosen variables) is similar to that of a vibro-impact process. The main attention is paid to properties of the limiting phase trajectories (LPTs) describing intensive energy exchange between the oscillator and external force. We show that two dynamical transitions occur in the undamped system under consideration with increasing parameter of nonlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Recently, the LPT ideas have been applied to the analysis of resonance-forced vibration [3,4] but an explicit expression of the LPT of a single oscillator in terms of elliptic functions is prohibitively difficult for practical utility. The purpose of the present paper is to show that a closed-form asymptotic solution can be obtained for a class of problems that are associated with the maximum energy exchange, and introduce relevant techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the LPT ideas have been applied to the analysis of resonance-forced vibration [3,4] but an explicit expression of the LPT of a single oscillator in terms of elliptic functions is prohibitively difficult for practical utility. The purpose of the present paper is to show that a closed-form asymptotic solution can be obtained for a class of problems that are associated with the maximum energy exchange, and introduce relevant techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This represents a second independent first integral of motion of the slow flow (15), in addition to the energy-conservation first integral (16). Before proceeding to a more detailed analytical treatment of the dynamics on the two-torus (19a) and (19b) we discuss the bifurcations that occur in this system as the parameter μ changes.…”
Section: Slow Flow Reduction Of the Dynamicsmentioning
confidence: 99%
“…(9). As shown in [7] and then in [8,[15][16][17][18], a unified description of highly non-stationary resonance dynamics can be performed by introducing the concept of LPT. This concept is important for understanding resonant energy exchange and non-stationary energy localization phenomena caused by the strong geometric nonlinearity in the system.…”
Section: Slow Flow Reduction Of the Dynamicsmentioning
confidence: 99%
“…Recent studies [2] have shown that the NNM approach is effective in the case of weak energy exchange, while the concept of the limiting phase trajectories (LPT) can be used to describe intense energy exchange between weakly coupled oscillators or oscillatory chains, or targeted energy transfer from a source of energy to an oscillator. Recently, the LPT concept has been applied to study resonance energy transfer from a source of harmonic excitation to the Duffing oscillator, and the precise solution of the LPT problem have been obtained [3,4]. However, the precise solution expressed in terms of elliptic functions is * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%